PROFIL PEMECAHAN MASALAH SISWA KELAS VII SMP NEGERI 2 PALU PADA SOAL CERITA PENJUMLAHAN DAN PENGURANGAN BILANGAN BULAT DITINJAU DARI GAYA BELAJAR - Muhamad Wali Kusumajoyo Krisno; Nurhayadi Nurhayadi; I Nyoman Murdiana (Universitas Tadulako, 2025)
This research aims to describe students' problem solving profiles in solving story problems adding and subtracting integers based on learning styles (visual, auditory and kinesthetic) using the Polya approach. This research uses a qualitative approach with descriptive methods. The research subjects consisted of three class VII students at SMP Negeri 2 Palu, each of whom represented a visual, auditory and kinesthetic learning style. The results of the research showed that students with a visual learning style did not fully understand the problem according to the Polya procedure, even though they could state some of the information in words. -said himself. Subjects prepare plans logically and carry out steps systematically, but do not double-check the results so that there are errors that are not corrected. Students with an auditory learning style can understand problems completely and formulate plans by adding up information based on time sequence. Subjects executed plans consistently but did not thoroughly double-check results, resulting in errors being left uncorrected. On the other hand, students with a kinesthetic learning style show good understanding, prepare appropriate plans, carry out steps systematically, and recheck the results according to Polya procedures, so that they get the correct answers and are confident in the results. This research provides insight into the influence of learning styles on mathematical problem solving abilities and the importance of paying attention to the re-examination step in the learning process.